Mental health and ethics: The concept of “sense of community” in Alfred Adler´s psychology - Oberst, Úrsula (2002)
This study defines Adler’s concept of “sense of community” and its ethical consequences equating it to mental health. The beginnings of individual psychology and the differences with orthodox psychoanalysis are analyzed to lead to the humanistic and social vision Adler has of persons and their psychological complexity. For Adler the sense of community constitutes the ethical framework that provides value to human activity. Basic concepts of Adler’s psychology are further discussed in order to define mental health as the intensity of the sense of community that a person has, which becomes a reference point and not an absolute truth. The sense of community is something one should aspire “as if” (Als ob) it were realizable.